Energy Prices and Households’ Incomes Growth Proportions in Russia’s Case Context - Morozko, Nina; Morozko, Natalia; Didenko, Valentina (International Journal of Energy Economics and Policy, 2021)
The article describes the past and future energy and natural resources policies in Russia. The authors consider the main trends and prospects in the state energy policy. The article shows the relationship between the National Welfare Fund growth and the decline in consumption. The authors argue the ability of raw materials revenues to solve problems of social financing. The analysis relies on the VAR and VECM-model to test the generated hypotheses. The model explores changes in energy prices in proportion to changes in individual factors of social and savings policies, taking into account the random component. We take the two most important elements of population income - these are social payments and wages. The article provides an opportunity to reflect on the ability of the innovative distribution of oil and gas revenues to change current social policies. The study complements our knowledge of the lack of social financing and the need to increase the real level of income. Keywords: energy prices, oil revenues, social benefits, wages JEL Classifications: E21, E25 DOI: https://doi.org/10.32479/ijeep.11147